2009
DOI: 10.1007/s11250-009-9389-5
|View full text |Cite
|
Sign up to set email alerts
|

Current situation of Peste des petits ruminants (PPR) in the Sudan

Abstract: The current situation of PPR in Sudan was investigated. A total of 61 tissue samples were collected from various PPR suspected outbreaks in sheep in Sudan during 2008. Collected tissue samples were tested for PPR antigen using IcELISA, PPR antigen was detected in 26 out of 61 samples (42.6%). Highest antigen detection rate was in specimens collected from western Sudan. A total of 1198 serum samples were collected from sheep (n = 500), camels (n = 392), and goats (n = 306) from different areas in Sudan (Khartou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 10 publications
0
28
3
Order By: Relevance
“…2a). Clearly both lineages III and IV are circulating in the Sudan and further serological reports from the country have confirmed outbreaks of PPRV in Sudan (Osman et al, 2009;Saeed et al, 2010). Swai et al (2009) recently confirmed natural transmission of PPRV and circulation of virus within herds in Tanzania.…”
Section: Africamentioning
confidence: 83%
“…2a). Clearly both lineages III and IV are circulating in the Sudan and further serological reports from the country have confirmed outbreaks of PPRV in Sudan (Osman et al, 2009;Saeed et al, 2010). Swai et al (2009) recently confirmed natural transmission of PPRV and circulation of virus within herds in Tanzania.…”
Section: Africamentioning
confidence: 83%
“…57,59,62,65,66,67,68,70,72,74,79,80,81,84,86,87,88,89,90,93,94,95,97,98,99,105,106,109,112,113,114,116,117,118,119,120,121,125,126,128,130,131,132,133,135,137,138,139,141,142,145,147,…”
Section: Study Eligibility Form: Performance Of Diagnostic Tests For mentioning
confidence: 99%
“…In 1997, a PPRV was isolated from pathologic samples collected during a rinderpest-like disease outbreak among buffalo in India ( 14 ). In September 2004, outbreaks of PPRV in Sudan affected both sheep and camels ( 15 , 16 ). In camels, a respiratory syndrome was the prominent disease characteristic observed, resembling a previous case reported in Ethiopia during 1995–1996 ( 17 ).…”
mentioning
confidence: 99%